Penerapan Model Inventori dengan Waktu Diskret dan Leadtime Pada Permasalahan Persediaan Daging Beku - Eka Susanti; Des Alwine Zayanti; Endro Setyo Cahyono; Novi Rustiana Dewi; Oki Dwipurwani; Dian Cahyawati Sukanda; Muhammad 'Aqil (Jurnal Sains Matematika dan Statistika, 2023)
Inventory management is needed to ensure product availability and minimize the risk of loss, especially for perishable products. This study aims to determine the optimal supply of frozen meat that minimizes total costs using the analytical matrix method. The concept of Quasi-Birth-Death with discrete time and leadtime is applied for analytic matrix calculations. The results obtained were an increase in inventory levels in each inventory period with an average increase of 2.4336% and an average increase in total costs of 17.2056%.